Code Switching Used by Teacher in Teaching English at SMP Negeri 3 Palopo - Cindy Clarissa Aris; Sri Damayanti S.; Reski Yusrini Islamiah Yunus (Universitas Cokroaminoto Palopo, 2022)
This study examined the types of code switching used by an English teacher and the reasons the teacher applied code switching in teaching English at SMP Negeri 3 Palopo. Using a descriptive qualitative design, the data were collected in August 2022 through classroom observation, video recording, and a structured interview with the eighth-grade English teacher. The observation was conducted in three classes for three 60-minute meetings, and the data were transcribed, reduced, classified, and interpreted based on Poplack's typology of code switching. The findings showed that intra-sentential switching was the most dominant type with 81 occurrences, followed by inter-sentential switching with 41 occurrences and tag switching with 12 occurrences. The teacher used code switching to clarify classroom instructions, explain vocabulary and grammar, reduce students' confusion, and help students understand learning tasks. The study concludes that code switching functions as a pedagogical strategy for facilitating English learning, particularly in junior high school contexts where students' English proficiency is still developing.